The design of everyday things - Norman, Donald A. (New York : Doubleday, 1988)
This book is about: The psychopathology of everyday things; The psychology of everyday actions; Knowledge in the head and in the World; Knowing what to do; ...
Keywords: Design; Human engineering; Industrial; Design, Industrial -- Psychological aspects; Human engineering